The Babushka Concept– An Instructional Sequence to Enhance Laboratory Learning in Science Education - Sofie Gårdebjer; Anette Larsson; Tom Adawi (Journal of Education in Science, Environment and Health)
This paper deals with a novel method for improving the traditional “verification” laboratory in science education. Drawing on the idea of integrated instructional units, we describe an instructional sequence which we call the Babushka concept. This concept consists of three integrated instructional units: a start-up lecture, a laboratory session and a wrap-up lecture. Like the Russian nested doll, the sequence has a nested conceptual structure, moving from “bigger” questions to “smaller” ones. The students are actively involved during the lectures by answering reflective questions. This careful sequencing of ideas and activities aims to help the students to relate new ideas to prior knowledge, and to understand the purpose of the laboratory activity. The Babushka concept was implemented in a master’s course in pharmaceutical technology and its impact was evaluated using both qualitative and quantitative methods. The evaluation focused on the students’ perceptions of the intervention as well as their learning gains. A majority of the students found the Babushka concept helpful for their learning and agreed that this concept should be used in other courses. Moreover, the number of correct answers on the final written exam increased by 10%. We briefly discuss one way to enhance the Babushka concept.